A study on legal framework for termination of strata scheme in Malaysia: challenges ahead / Nor Asiah Mohamad - Mohamad, Nor Asiah (2014)
The purpose of this paper is to analyse the legal provisions on termination of strata scheme under the Malaysian strata law. The study uses semi qualitative legal analysis approach where the provisions of the related laws are examined to see the specific requirement for the termination of strata scheme and the challenges. In this process, a comparison of similar provisions will be made with other jurisdictions in particular, New South Wales, Australia and Singapore. This study analyses reported and unreported case law in order to see the common issues of objection in the process of termination. The findings show that there are specific provisions dealing with termination of subdivided properties in Malaysia where unanimous agreement is required. This state of law is different from the development in other jurisdictions, which provide for no unanimity requirement in strata termination. There is also latest change in the Strata Titles Act 1985 with regards to distribution of profits on termination of subdivision which is based on open market capital values of parcels while previously it was based on share units. The outcome of the study would help to prepare for future enhancement of the law and its implementation in Malaysia.